(3EedGA dYHO Gddg Hf MeRIs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3aUd , ePgHfG Cf YJQg GdQShd Udi Gddg Ydjg hBdg ge Ydi haGWeI hGdMSf hGdMSjf hChdGOgeG s
(3BNQgG (B:s
(3hGdCNHGQ GdhGQOI cKjQI hGVMI , CVQHfG Yf PcQgG cQGgI ddEWGdI Je Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3cJHJ GdYfGhjjf HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
Keywords: (3GdJhMjO hGdedd hGdfMds